Leading Commodities of Food Crops and Plantation Subsector in Pinrang District - St Aisyah Ramli; Sitti Khadijah Yahya Hiola (Agriekonomika, 2019)
This study aims to determine the food crop and plantation subsectors which are the leading subsectors in Pinrang District. The determination analyzed using the Location Quotient method which produces commodities classified as a base or non-base commodities which can contribute to increasing farmer income and regional income. The data sources used are primary data from interviews with farmers while secondary data on food crop and plantation production in Pinrang District for five years (2013-2017) were obtained from the Agriculture Service and BPS of Pinrang District. The results show thatthe food crop subsector is a base commodity and is very potential, namely wetland paddy and maize which have a base area in five sub-districts in Pinrang District. Whereas in the plantation sub-sector which is the basis, namely coconut, coffee, and cocoa, although the highest LQ value is in coffee commodities in Lembang subdistrict. Thus, commodities in the food crops and plantation sub-sectors are basic commodities that are worth developing. Pinrang District is one of the rice barns in South Sulawesi, which holds the position of Pinrang District as a potential producer of food crops. In addition to wetland paddy, other food crops produced are maize and beans. The most dominant plantation crops in Pinrang District are coconut, coffee, and cocoa, which are excellent crops.